Green Mining Efficiency and Improvement Countermeasures for China's Coal Mining Industry - Wang, Ying; Lei, Yuxuan; Wang, Shuyi (Frontiers in Energy Research, 2020)
This study defines a green mining system as a synergetic operation system composed of a mining subsystem and an environmental governance subsystem. Through conducting a case study of China's coal enterprises, this study identifies the mining subsystem as the first production stage and the environmental governance subsystem as the second production stage. To evaluate green mining efficiency, an entire green mining efficiency indicator system was constructed by analyzing the main inputs and outputs of the two subsystems. Using the 2019 data collected from Chinese coal mining enterprises based on the constructed indicator system, this study presents a two-stage combination Data Envelopment Analysis model to assess green mining efficiency in terms of mining efficiency and environmental governance efficiency. According to this empirical study's results, there were four main findings. First, coal enterprises can be divided into three categories in accordance with the efficiency value ranking generated by the two-stage model and the corresponding synergetic development levels. Second, the percentage distribution of coal enterprises based on their green mining efficiency level embodies the attributes of a spindle structure. Third, the exported parameters information from the two-stage model supports green mining efficiency improvement as quantitative evidence. Fourth, the model results form the basis for policy proposals and improvement countermeasures.